Local wound healing biomarkers for real‐time assessment of periodontal regeneration: pilot study. (11th August 2016) - Pellegrini, G.; Rasperini, G.; Pagni, G.; Giannobile, W. V.; Milani, S.; Musto, F.; Dellavia, C.
Abstract : Background and Objectives: Within the same surgical procedure, a great variability on achievement of clinical outcomes exists and may be associated to different molecular factors related to tissue healing. The aim of the present study was to assess the distribution of clinical success separately in regenerative therapy (REG) and open flap debridement (OFD) to evaluate if factors related with healing of epithelium, connective tissue and bone may be associated to the clinical outcome within each surgical procedure. Material and Methods: Sixteen patients underwent periodontal REG and nine patients underwent OFD. Periodontal wound fluid was collected at baseline, 3–5, 7, 14 and 21 d after surgery, and expression of wound healing proteins was assessed. Pocket depth and clinical attachment level were taken at baseline and at 6 mo of follow‐up. Percentage pocket depth reduction and percentage clinical attachment level gain were computed. Patients were regarded as better or worse responders depending on their percentage pocket depth reduction or percentage clinical attachment level gain. Results: Higher percentage of better responders was observed in the REG group (68.7%) compared to the OFD group (22.2%). At 21 d, no difference in the profile of most of the proteins emerged, with two exceptions, both regarding REG treatment. Bone morphogenetic protein‐7 tended to increase in better responders and to decrease in worse responders. Matrix metalloproteinase‐1 increased in worse responders and remained substantially unchanged in better responders. Conclusion: Local expression of matrix metalloproteinase‐1 and bone morphogenetic protein‐7 during wound healing is associated with the clinical performance of periodontal regenerative surgery. The use of local biomarkers offers the potential for real‐time assessment of the periodontal healing process.